THE DIFFERENCES OF COPING MECHANISM IN EXTROVERT AND INTROVERT PERSONALITY CHARACTERISTICS - RAHMAWATI, RAHMAWATI; AGUS ARIE AFFANDIE, AGUS ARIE AFFANDIE; AULA ISNAINIME, AULA ISNAINIME (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2013)
Students have a lot of work in their daily life , the challenges and demands that must be executed . Lack of understanding of the above makes student anxiety , stress , and even withdraw dependent . This study aimed to differences in coping mechanisms with extrovert and introvert personality traits in the Academy of Health Rajekwesi Bojonegoro .       This type of research using comparative designs , The Sample was student of health nursing Academy  Rajekwesi Bojonegoro , its amount 79 respondents choosen with proportionate stratified random sampling . The independent variable is Ekstrovert and introvert personality characteristic and the dependent sample is coping mechanism. The analyze of data using Chi Square Test.       The results showed that the majority of respondents who have extrovert personality traits with destructive coping mechanisms  ( 72.6 % ) and who have introvert personality  53.0 %  . The results of Chi-Square test  was 0.123.       The conclusion was no differences between coping mechanisms with extrovert and introvert personality traits . This is caused by environmental factors that makes no distinction between extrovert and introvert personality traits . With positive thinking and self-control in solving of problems , so that students can correct coping mechanisms become constructive . Keywords : Coping mechanism, Ektrovert and Introvert Personality .